2004
DOI: 10.1080/1354983042000246252
|View full text |Cite
|
Sign up to set email alerts
|

The Cities for Climate Protection Campaign (CCPC) and the framing of Local Climate Policy

Abstract: The paper contributes to the research on understanding local global warming politics. Strategic documents from The Cities for Climate Protection Campaign (CCPC) are analysed to show how CCPC has constructed climate change protection as a local issue. The paper's premise is that the climate change issue must be translated or framed to enable actors to work with this problem in a local context, and that successful framing requires establishing a coherent method of describing social reality. CCPC emphasises that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
124
0
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(133 citation statements)
references
References 8 publications
1
124
0
8
Order By: Relevance
“…on their commitments (Lindseth, 2004). This is also seen in the UK, where despite were analysed within the economic structure category.…”
Section: Dependent Variable -'Action Index' On Climate Changementioning
confidence: 77%
See 2 more Smart Citations
“…on their commitments (Lindseth, 2004). This is also seen in the UK, where despite were analysed within the economic structure category.…”
Section: Dependent Variable -'Action Index' On Climate Changementioning
confidence: 77%
“…Despite the absence of Federal government engagement with climate change policy, 565 municipal governments have currently signed up to CCP (ICLEI, 2011). Studies have found involvement to be linked to local environmental issues such as air quality (Betshill, 2001;Lindseth, 2004), whilst Zahran et al (2008a;2008b) found that factors related to a municipal area's geographic location and socioeconomic structure variously motivated or discouraged engagement with the programme.…”
Section: Local Government Action On Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…Innovations of this type are more likely to be influenced by scientific and technical information and stakeholder negotiations. Policy entrepreneurs often play a considerable strategic role in pushing the issue forward onto the political agenda (Bulkeley and Betsill 2003;Deyle et al 1994;Kingdon 1995;Lindseth 2004). We found that all cities that have developed and implemented CAPs have integrated stakeholder participation into the planning process to varying degrees.…”
Section: Resultsmentioning
confidence: 96%
“…Framing it as a national or global issue, the dominant approach right now, may make it more difficult for individuals to understand why climate change may be relevant for them personally or for their local community or city. Against this background, the campaign Cities for Climate Protection (CCPC) (Lindseth 2004) which has taken the local level as the relevant geographical space for climate protection may be an effective approach to organize responses to climate change. Not only spatial but also other frames such as those relating to time dimensions may affect responses to climate change.…”
Section: Implications For Climate Policymentioning
confidence: 99%